2020
DOI: 10.2147/ijgm.s285003
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations of Interleukin 10, Matrix Metallopeptidase 9, and Legumain with Blood Pressure Variability and Neurologic Outcomes in Patients with Ischemic Stroke</p>

Abstract: Background Timely diagnosis and treatment are crucial to improve prognosis of ischemic stroke, making exploring factors associated with prognosis essential. Blood pressure variability (BPV) was reported to be associated with neurologic outcome, and basic researches on cardiovascular diseases found abnormal expression patterns of several factors including interleukin 10 (IL-10), matrix metallopeptidase 9 (MMP-9), and legumain which might be related to abnormal BPV but yet to prove in ischemic strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…According to earlier research, interleukin (IL)‐10 may be able to control inflammation by lowering the expression of cytokines and preventing receptor activation. Known as a cytokine production inhibitory factor, IL‐10 has been shown to ameliorate vascular disorder, inactivate numerous cells, impair effector functions, and lessen endothelial cell damage 208–211 . As a result, IL‐10 has immunomodulatory effects throughout an inflammatory response and has an anti‐inflammatory role in the inflammatory response following stroke.…”
Section: Engineered Mscs In Strokementioning
confidence: 99%
“…According to earlier research, interleukin (IL)‐10 may be able to control inflammation by lowering the expression of cytokines and preventing receptor activation. Known as a cytokine production inhibitory factor, IL‐10 has been shown to ameliorate vascular disorder, inactivate numerous cells, impair effector functions, and lessen endothelial cell damage 208–211 . As a result, IL‐10 has immunomodulatory effects throughout an inflammatory response and has an anti‐inflammatory role in the inflammatory response following stroke.…”
Section: Engineered Mscs In Strokementioning
confidence: 99%
“…In a mouse model mimicking chronic cerebral hypoperfusion, the depletion of legumain improved cognitive impairment by reducing neuroinflammation, as legumain is upregulated and triggers synaptic plasticity impairment and neuroinflammation [114]. In newly diagnosed progressive ischemic stroke patients, circulatory legumain was significantly higher than in patients with nonprogressive ischemic stroke but was not correlated with blood pressure variability and neurological outcome [115]. In addition, it is shown that legumain contributes to the immune responses during stroke by indirectly altering the number of CD74+ cells in the ischemic hemisphere by the modification of molecules involved in immune cell attraction [72].…”
Section: Role Of Legumain In Vascular Homeostasis Cardiovascular and ...mentioning
confidence: 99%
“…Furthermore, increased serum IL-10 and MMP-9 was observed in patients with IS, among which IL-10 was found to play an important anti-inflammatory role in responding to brain injury. [18][19][20][21] Previous study showed that carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) played a crucial role in the immune regulation. 22,23 As a member of the immunoglobulin superfamily, CEACAM1 is known as an inhibitory immune co-receptor suppressing the signal transmission via two immunreceptor tyrosine-based inhibition motifs.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, MMP‐9 was considered to play an important role in the BBB injury after IS, while the MMP‐9 inhibitor provided protection against potential alternations in BBB permeability. Furthermore, increased serum IL‐10 and MMP‐9 was observed in patients with IS, among which IL‐10 was found to play an important anti‐inflammatory role in responding to brain injury 18–21 . Previous study showed that carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) played a crucial role in the immune regulation 22,23 .…”
Section: Introductionmentioning
confidence: 99%